Fundamental research on iron coke hot briquette – A new type burden used in blast furnace. (13th September 2016) - Wang, H.; Chu, M.; Zhao, W.; Wang, R.; Liu, Z.; Tang, J.
Abstract : In order to improve blast furnace efficiency, reduce CO2 emission and accelerate energy utilisation, a new preparation process of iron coke hot briquette (ICHB) based on the raw materials conditions in China, a new type blast furnace ironmaking burden, was experimentally investigated in this paper. The new preparation process was researched and optimised through single factor experiment and orthogonal experiment. Meanwhile, the reactivity and the post-reaction strength of ICHB prepared under the optimised conditions were tested and the effect of ICHB on the thermal performance of conventional coke was researched. In addition, softening and dripping properties of mixed burden with optimised ICHB charging was simultaneously investigated. The results showed that the optimised preparation parameters of ICHB include 15% iron ore, 65% bituminous coal, 350°C hot briquetting temperature, 1100°C carbonisation temperature and 4 hours carbonisation time. The reactivity and the post-reaction strength of ICHB prepared under the optimisation conditions are 62.4 and 10.6%, respectively. ICHB has protective effect on conventional coke and the protective effect is more obvious with 10% ICHB adding. With the increase of ICHB charging ratio, softening interval T 40 – T 4 of mixed burden is widened while melting interval T D – T S (namely cohesive zone) is narrowed. Additionally, the permeability of mixed burden becomes better and dripping ratio is first increased then decreased. The suitable charging ratio of ICHB in mixed burden is about 30%.